2023
DOI: 10.1021/acsaelm.3c00118
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Molecular Aggregation and Photoresponse of Narrow-band Organic Photodetectors

Abstract: It is a great challenge to find suitable organic materials for developing narrow-band absorption organic photodetectors (NBA-OPDs) working in the deep-red and near-infrared spectral regions. In general, if dye molecules can form J-aggregates, their maximal absorption peak will red-shift and become narrower. In this work, a suitably structured pyrrolopyrrole cyanine (PPCy) with this unique property is realized for use in narrow-band photodetectors. It was found that the Coulomb and charge-transfer (CT) coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Assuming that the loose particle noise is the main noise under reverse bias, the D * is calculated by the following equation, 38,65 where q is the electric quantity carried by unit charge.…”
Section: Resultsmentioning
confidence: 93%
“…Assuming that the loose particle noise is the main noise under reverse bias, the D * is calculated by the following equation, 38,65 where q is the electric quantity carried by unit charge.…”
Section: Resultsmentioning
confidence: 93%
“…The value of D * is measured as the output signal-to-noise ratio relative to the detection region. Given the sufficient low spectral noise density, shot noise was identified as the primary source affecting D * . PS is defined as the current variation due to light-induced EHPs.…”
Section: Resultsmentioning
confidence: 99%
“…According to our previous research, PPCy tends to form an "edge-on" arrangement on silicon wafers. 40 Therefore, the difference in film thickness (H + l) of these three molecules was mainly attributed to the hindrance caused by their different coordination structures, resulting in different slip angles (γ) along the Y-axis direction during molecular stacking (Figure 3). This also aligned with the theoretical calculation results (Figure 2d−f).…”
Section: Microscopic Studymentioning
confidence: 99%
“…To date, a few organic dye J-aggregates have been identified, such as cyanine dyes, porphyrin derivatives, BODIPY, and perylene bisimides. , Meanwhile, the repertoire of molecules capable of forming J-aggregates remains limited, and research elucidating the underlying mechanisms driving J-aggregate formation is also scarce. The PPCy dyes bear a structural resemblance to cyanine dyes and BODIPY, exhibiting similar physical properties like robust NIR absorption, high QY, and excellent photostability. Recent studies have demonstrated the potential of PPCy dyes to form J-aggregates, which have been extensively utilized for applications of FLI, PTT, and photoacoustic imaging. Nevertheless, the relationship between the molecular structure of PPCy and the resulting aggregate structure, as well as the physical properties of these aggregates, remains poorly understood. Furthermore, it is worth noting that these aggregates solely contribute to enhancing the FLI or PTT performance.…”
Section: Introductionmentioning
confidence: 99%